2008
DOI: 10.1016/j.ajog.2007.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Plasma of pregnant and preeclamptic women activates monocytes in vitro

Abstract: Plasma of both pregnant women and women with preeclampsia activated monocytes in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…9,13,14,16 There are many substances which can stimulate an inflammatory response in normal pregnancy and preeclampsia, such as, angiogenic factor, cytokines, product of oxidative stress, and microparticle trophoblasts. 4,12,17 Faas et al 18 , in their 2008 study show that plasma from normal pregnancy and preeclampsia could activate monocytes in vitro. 16,19e22 The inflammatory response involves various transcription factors.…”
Section: Introductionmentioning
confidence: 97%
“…9,13,14,16 There are many substances which can stimulate an inflammatory response in normal pregnancy and preeclampsia, such as, angiogenic factor, cytokines, product of oxidative stress, and microparticle trophoblasts. 4,12,17 Faas et al 18 , in their 2008 study show that plasma from normal pregnancy and preeclampsia could activate monocytes in vitro. 16,19e22 The inflammatory response involves various transcription factors.…”
Section: Introductionmentioning
confidence: 97%
“…A recent review summarized the current knowledge on maternal monocytes in preeclampsia and concluded that monocytes play a role in normal pregnancy and preeclampsia . An increase in peripheral blood monocytes and an altered activation status of these monocytes in preeclampsia as compared to healthy pregnancy has been suggested . However, monocytes are heterogeneous, and the role of the different populations in pregnancy is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Повышение экспрессии молекулы CD54 клетками линии ТНР-1 под влиянием факторов, секретируемых тканью плаценты при физиологической беременности, как в первом, так и в третьем триместре, по сравнению со спонтанным уровнем свидетельствует об их активированном состоянии. Полученные на модели in vitro данные могут свидетельствовать в пользу активации моноцитов периферической крови матери при физиологической беременности, что согласуется с данными, описанными в литературе [7,19]. Уменьшение интенсивности экспрессии молекулы CD54 клетками линии ТНР-1 в присутствии секреторных продуктов плацент третьего триместра физиологической беременности по сравнению с первым триместром свидетельствует в пользу снижения степени активации моноцитов на поздних сроках беременности.…”
Section: Discussionunclassified
“…На ранних сроках физиологической беременности плацента активно развивается, и повышение уровня экспрессии TRAIL может быть направлено на обеспечение ремоделирования ткани плаценты [24]. В присутствии факторов, секретируемых тканью плаценты при гестозе, повышена экспрессия молекулы CD54 клетками линии ТНР-1 по сравнению со спонтанным уровнем, что соответствует данным, описанным в литературе об активации моноцитов при гестозе [4,7,20,26]. Гестоз характеризуется развитием воспалительной реакции в ткани плаценты, сопровождающейся увеличением количества мононуклеаров, инфильтрирующих децидуальную ткань плаценты [4,16,18,22].…”
Section: таблица 2 изменение интенсивности экспрессии исследуемых моunclassified